Electricity Consumption Dynamics in Indonesia: ARDL Approach - Thangraj Venkatesanirst; Suripto Suripto; Natasya Cut Dian Amelia; Azkal Azkiya Athfal (JAMPE (Journal of Asset Management and Public Economy), 2026)
This study analyzes the determinants of per capita electricity consumption in Indonesia using consumption expenditure, foreign direct investment (FDI), trade, and inflation over the period 1980–2022. Given the increasing electricity demand driven by economic growth and structural transformation, understanding these determinants is essential for sustainable energy planning. This study contributes by providing evidence on how macroeconomic variables affect electricity consumption differently in the short run and long run in Indonesia. The findings imply that energy policy should distinguish between short-term demand management and long-term supply planning. The results show that, in the short run, consumption expenditure and trade have a positive and significant effect on electricity consumption, while inflation has a negative and significant impact. FDI has no significant effect in the short term. In the long term, FDI and inflation have a positive and significant effect on per capita electricity consumption, indicating that foreign investment strengthens industrial and infrastructure capacity, thereby increasing energy demand. Consumption and trade spending are not statistically significant in the long run, which indicates that the impact is temporary. These findings imply that electricity demand in Indonesia is influenced by both cyclical and structural factors. Therefore, energy policy should differentiate between short-term demand stabilization and long-term planning, particularly by promoting productive investment and maintaining macroeconomic stability.